Sistem Informasi Akademik STKIP Hamzanwadi Selong Menggunakan Technology Acceptance Model - Jamaludin Jamaludin; Muhammad Khairu Rizal (Jurnal Pendidikan Informatika (EDUMATIC), 2017)
Academic Information System (SIAKAD) is one part that is very important for universities today. This can facilitate the access of a student in interacting with the campus. In addition, SIAKAD will also improve the competitiveness of these universities and will directly improve the institution's business processes. To optimize the academic information system, research must be conducted by evaluating the use of the system from the SIAKAD. This study is intended to evaluate the use of SIAKAD in STKIP Hamzanwadi Selong by using the Technology Acceptance Model (TAM) and to process the survey data using Partial Least Square software to measure user perceptions of SIAKAD whether it works according to its function. The data obtained is primary data using a questionnaire to students using SIAKAD which consists of several departments. The variables used are Perceived Ease of Use, Perceived Usefulness, Attitude towards Using Technology, Behavioral Intention to Use and Actual Technology Use. The results of this study indicate that SIAKAD SIAM has benefits and is easy to use by students as users, and all technology features in the SIAKAD application have benefits with the receipt of the Actual Technology Use Variable.